New perspectives on adobe dreamweaver CS4 : - Hart, Kelly (Course Technology, 2010)
Part of the New Perspectives Series, this title offers a case-based, problem-solving approach to learning Adobe Dreamweaver CS4. Includes extensive coverage on planning and designing a Web site.